Glucagon Effects on (3)H-Histamine Uptake by the Isolated Guinea-Pig Heart during Anaphylaxis - Rosic, Mirko (Hindawi Publishing Corporation, 2014)
We estimated the influence of acute glucagon applications on (3)H-histamine uptake by the isolated guinea-pig heart, during a single (3)H-histamine passage through the coronary circulation, before and during anaphylaxis, and the influence of glucagon on level of histamine, NO, O(2) (−), and H(2)O(2) in the venous effluent during anaphylaxis. Before anaphylaxis, glucagon pretreatment does not change (3)H-histamine Umax and the level of endogenous histamine. At the same time, in the presence of glucagon, (3)H-histamine Unet is increased and backflux is decreased when compared to the corresponding values in the absence of glucagon. During anaphylaxis, in the presence of glucagon, the values of (3)H-histamine Umax and Unet are significantly higher and backflux is significantly lower in the presence of glucagon when compared to the corresponding values in the absence of glucagon. The level of endogenous histamine during anaphylaxis in the presence of glucagon (6.9–7.38 × 10(−8)  μM) is significantly lower than the histamine level in the absence of glucagon (10.35–10.45 × 10(−8)  μM). Glucagon pretreatment leads to a significant increase in NO release (5.69 nmol/mL) in comparison with the period before glucagon administration (2.49 nmol/mL). Then, in the presence of glucagon, O(2) (−) level fails to increase during anaphylaxis. Also, our results show no significant differences in H(2)O(2) levels before, during, and after anaphylaxis in the presence of glucagon, but these values are significantly lower than the corresponding values in the absence of glucagon. In conclusion, our results show that glucagon increases NO release and prevents the increased release of free radicals during anaphylaxis, and decreases histamine level in the venous effluent during cardiac anaphylaxis, which may be a consequence of decreased histamine release and/or intensified histamine capturing by the heart during anaphylaxis.